2021
DOI: 10.3390/ijms222111942
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Immunotherapy Outcome in Advanced Lung Cancer

Abstract: In developed countries, lung cancer is the leading cause of cancer-related death in both sexes. Although cigarette smoking represents the principal risk factor for lung cancer in females, the higher proportion of this neoplasm among non-smoking women as compared with non-smoking men implies distinctive biological aspects between the two sexes. Gender differences depend not only on genetic, environmental, and hormonal factors but also on the immune system, and all these aspects are closely interconnected. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…Most patients with NSCLC in this study were retired. Recently, sex and age differences have been demonstrated to exert a direct influence on oncological treatments, specifically immunotherapy, with documented distinctions between men and women ( Vavalà et al., 2021 ). Consequently, to correctly assess cancer outcomes, a multicenter study with greater population is required in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with NSCLC in this study were retired. Recently, sex and age differences have been demonstrated to exert a direct influence on oncological treatments, specifically immunotherapy, with documented distinctions between men and women ( Vavalà et al., 2021 ). Consequently, to correctly assess cancer outcomes, a multicenter study with greater population is required in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed. All of these considerations may affect immunotherapy [ 111 ], and possibly statins or mevalonate pathway-acting compounds in co-treatment.…”
Section: Gender Influence On Statins’ Effect In Lung Cancermentioning
confidence: 99%
“…We also discovered a lower immune response rate in male NSCLC patients, while a higher immune response rate is observed in female NSCLC patients. Recent research has demonstrated that men and women respond differently to NSCLC and immunotherapy due to differences in the immune system (24). NSCLC cells may be exposed to a more effective immune surveillance mechanism when estrogen regulates the production of inflammatory cytokines from macrophages and neutrophils (25).…”
Section: Discussionmentioning
confidence: 99%